Implementasi Customer Relationship Management (CRM) dalam Strategi Pemasaran UMKM Berbasis Digital - Fitriany Fitriany; Yurisman Star (Yayasan Literasi Sains Indonesia, 2025)
Digital transformation requires MSMEs not only to rely on online promotion but also to manage customer relationships more systematically through the implementation of Customer Relationship Management (CRM). However, most MSMEs remain at the basic level in utilizing customer data, resulting in suboptimal digital marketing outcomes. This study aims to analyze the influence of CRM on MSME performance, both directly and indirectly through digital marketing strategies as a mediating variable. A quantitative survey was conducted involving 120 MSME actors in the culinary, fashion, and creative service sectors, using structured questionnaires and analyzed through simple and multiple regression. The findings indicate that CRM has a positive and significant impact on digital marketing strategies (β = 0.58) and MSME performance (β = 0.35), with an indirect effect through digital marketing mediation (β = 0.36). The data also reveal that social media is the most frequently used digital channel, while marketplace utilization, promotional applications, and customer database management remain limited. Digital marketing strategies significantly improve MSME performance (β = 0.62), particularly in terms of sales and customer loyalty. The study concludes that integrating CRM with digital marketing can enhance the competitiveness of MSMEs in the digital era. However, limitations related to sample size, sectoral scope, and the cross-sectional design restrict the generalizability of the findings, suggesting that future research should expand coverage and incorporate external variables such as digital literacy and policy support.